The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13041-018-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of temperature-sensitive leak K+ currents and expression of TRAAK, TREK-1, and TREK2 channels in dorsal root ganglion neurons of rats

Abstract: Leak K+ currents are mediated by two-pore domain K+ (K2P) channels and are involved in controlling neuronal excitability. Of 15 members of K2P channels cloned so far, TRAAK, TREK-1, and TREK-2 are temperature sensitive. In the present study, we show that strong immunoreactivity of TRAAK, TREK-1 and TREK-2 channels was present mainly in small-sized dorsal root ganglion (DRG) neurons of rats. The percentages of neurons with strong immunoreactivity of TRAAK, TREK-1 and TREK-2 channels were 27, 23, and 20%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…For example, heat perception in mammals is mediated by both the TRANSIENT RECEPTOR POTENTIAL (TRP) cationic channel family and the TWIK-RELATED POTASSIUM (TREK) channel family present in neurons. Increasing temperatures led to depolarization and increased action potential firing of corresponding neurons (Voets et al, 2004;Viatchenko-Karpinski et al, 2018). In Caenorhabditis elegans, high sodium levels result in an influx of Ca 21 and membrane depolarization mediated by TRANSMEMBRANE CHANNEL LIKE1 (TMC1;Chatzigeorgiou et al, 2013).…”
mentioning
confidence: 99%
“…For example, heat perception in mammals is mediated by both the TRANSIENT RECEPTOR POTENTIAL (TRP) cationic channel family and the TWIK-RELATED POTASSIUM (TREK) channel family present in neurons. Increasing temperatures led to depolarization and increased action potential firing of corresponding neurons (Voets et al, 2004;Viatchenko-Karpinski et al, 2018). In Caenorhabditis elegans, high sodium levels result in an influx of Ca 21 and membrane depolarization mediated by TRANSMEMBRANE CHANNEL LIKE1 (TMC1;Chatzigeorgiou et al, 2013).…”
mentioning
confidence: 99%
“…Previous studies described menthol as being promiscuous in its targets with the possibility of modulating the activity of other thermosensors (TRPA1, TRPV3, TRPC5, Nav1.9 and two pore potassium channels) [11,26,28,44]. Yet, menthol inhibits the activity of most of these channels at the concentrations used, including TRPA1 which was considered to be a noxious cold sensor [11,[26][27][28]44]. At the molecular level, we found that MOR activation by morphine leads to a PKCβ-induced reduction of TRPM8 desensitization likely via phosphorylation of the two Ser residues 1040 and 1041.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, no significant change in mRNA expression was found for either TRPM8 or other cold sensitive TREK-1 and TRAAK channels ( Fig. S1c), implying a functional rather than transcriptional regulation of these neurons [11,[26][27][28].…”
Section: Chronic Morphine Reduces Both Cold and Menthol-evoked Desensmentioning
confidence: 91%
“…Previous studies described menthol as being promiscuous in its targets with the possibility of modulating the activity of other thermosensors (TRPA1, TRPV3, TRPC5, Nav1.9 and two pore potassium channels) [11,26,28,44]. Yet, menthol inhibits the activity of most of these channels at the concentrations used, including TRPA1 which was considered to be a noxious cold sensor [11,[26][27][28]44]. At the molecular level, we found that MOR activation by morphine leads to a PKCβ-induced reduction of TRPM8 desensitization likely via phosphorylation of the two Ser residues 1040 and 1041.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, no significant change in mRNA expression was found for either TRPM8 or other cold sensitive TREK-1 and TRAAK channels ( Fig. S1c), implying a functional rather than transcriptional regulation of these neurons [11, [26][27][28].…”
Section: Chronic Morphine Reduces Both Cold and Menthol-evoked Desensmentioning
confidence: 99%